Multi-omics analysis of gestational PM2.5 exposure induces abnormal cardiac metabolism and development in offspring - Li Tian; Qinglin Sun; Jianong Lv; Shiqian Liu; Kexin Zhang; Yang Li; Zhiwei Sun; Lili Cao; Junchao Duan (Ecotoxicology and Environmental Safety)
Epidemiological evidence suggests that exposure to ambient fine particulate matter (PM2.5) during pregnancy may increase the risk of congenital heart disease; however, the underlying mechanisms remain unclear. This study aimed to investigate the effects of gestational PM2.5 exposure on offspring cardiac development and to elucidate the potential mechanisms involved. Gestational exposure to PM2.5 significantly reduced litter size, birth weight, and offspring cardiac mass. Further analyses revealed inflammatory infiltration, lipid peroxidation, and decreased ATP levels in the offspring hearts, indicating impaired energy metabolism. Transcriptomic and proteomic analyses showed that differentially expressed genes and proteins were primarily enriched in pathways related to mitochondrial function, cardiac development, and ATP metabolism. Metabolomic profiling demonstrated significant downregulation of alpha-ketoglutaric acid, with key metabolites enriched in aspartate and glutamate metabolism, the tricarboxylic acid (TCA) cycle, and ferroptosis. Integrative multi-omics analysis further revealed that gestational PM2.5 exposure disrupted multiple metabolic pathways in the offspring heart, including the TCA cycle, glycolysis/gluconeogenesis, and propanoate metabolism. Gene–metabolite co-expression network analysis identified several key mitochondrial regulators—Sirt3, Lonp1, Tfam, Mfn2, and Sirt5—as central mediators of metabolic reprogramming in response to PM2.5 exposure, through modulation of 12 metabolites. Moreover, findings from multiplex immunohistochemistry and RT-qPCR analyses were consistent with the multi-omics results. In conclusion, our study suggests that gestational exposure to PM2.5 induces energy metabolism dysfunction and abnormal cardiac development in offspring.